Generation of high-energy-density collimated electron-positron beam by a linear polarized laser-plasma interaction from a cone. (September 2020) - Shan, Fei; Ma, Yanyun; Yang, Xiaohu; Zhang, Guobo; Tian, Lichao; Jiang, Jing; Li, Xiaoxiao; Ma, Long; Yuan, Yun; Han, Peng; Cui, Ye
Abstract: Electron-positron plasma has attracted much attention recently due to their unique properties. In this paper, we study the acceleration of electron-positron plasma in a cone by using PIC method. The electrons and positrons will be scattered by transverse ponderomotive force during the interaction between laser and electron-positron plasma. A new scheme is proposed to obtain high-energy dense collimated electron-positron plasma by a hollow gold cone. Transverse scattered electrons and positrons are pinched in the gold cone. Both electrons and positrons can be accelerated by ponderomotive force continuously and a dense collimated electron-positron plasma is produced. The energy of electrons and positrons obtained in the cone is much higher than the upper limit of electron energy obtained by ponderomotive force acceleration. The high quality electron and positron beam has great potential value in further research.